Processing, physico-chemical characterisation and in vitro evaluation of silicon containing β-tricalcium phosphate ceramics - Detsch, Rainer; et al. (Materials Science and Engineering C, 2011)
For bone grafting applications, the elaboration of silicon containing beta-tricalcium phosphate (β-TCP) was studied. The synthesis was performed using a wet precipitation method according to the hypothetical theoretical formula Ca(PO)(SiO ). Two silicon loaded materials (0.46 wt.% and 0.95 wt.%) were investigated and compared to a pure β-TCP. The maturation time of the synthesis required in order to obtain β-TCP decreased with the amount of silicon. Only restrictive synthesis conditions allow preparing silicon containing β-TCP with controlled composition. To obtain dense ceramics, the sintering behaviour of the powders was evaluated. The addition of silicon slowed the densification process and decreased the grain size of the dense ceramics. Rietveld refinement may indicate a partial incorporation of silicon in the β-TCP lattice. X-ray photoelectron spectroscopy and transmission electron microscopy analyses revealed that the remaining silicon formed amorphous clusters of silicon rich phase. The in vitro biological behaviour was investigated with MC3T3-E1 osteoblast-like cells. After the addition of silicon, the ceramics remained cytocompatible, highlighting the high potential of silicon containing β-TCP as optimised bone graft material. © 2010 Elsevier B.V. All rights reserved.
Keywords: In vitro evaluation; Powder synthesis; Silicon; Sintering; Tricalcium phosphate